풀이
import java.util.*;
class Solution {
public int solution(int[][] data, int col, int row_begin, int row_end) {
int answer = 0;
int idx = col-1;
Arrays.sort(data, (o1, o2) -> o1[idx]!=o2[idx] ? o1[idx] - o2[idx] : o2[0] - o1[0]);
List<Integer> list = new ArrayList<>();
for (int i= row_begin; i<=row_end; i++){
int sum =0;
for(int j=0; j<data[i-1].length; j++){
sum += (data[i-1][j] % i);
}
list.add(sum);
}
int xor = list.get(0);
for(int i=1; i<list.size(); i++){
xor ^= list.get(i);
}
return xor;
}
}